A new Pteroncola species (Bacillariophyceae) from the South Shetland Islands, Antarctica - Almandoz, Gaston Osvaldo; Ferrario, Martha Elba; Sullivan, Michael J.; Ector , Luc; Schloss, Irene Ruth (Phycologia)
The marine araphid diatom Pteroncola carlinii sp. nov. from a coastal Antarctic environment was described based on light and scanning electron microscopy observations. The new species was found as solitary cells in the phytoplankton and epiphytic on green algal filaments or diatom chains. It was distinguished from P. inane, the only recognized species, primarily by a well developed sternum, a hyaline mantle, apical pore fields composed of three horizontal rows of pores, a single rimoportula per valve, and a lower striae density. Two morphotypes of P. carlinii were distinguished based upon the ultrastructure of alveolate (chambered) striae in external view. While most specimens presented striae formed by transapically elongated slits, others showed striae composed of a row of small areolae. A revised description of Pteroncola was provided as well as a comparison with related genera in the Fragilariaceae, such as Brandinia, Catacombas, Fragilaria, Fossula, Hyalosynedra, Staurosirella and Thalassioneis. Fil: Almandoz, Gaston Osvaldo. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Division Ficología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ferrario, Martha Elba. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Division Ficología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Sullivan, Michael J. Fil: Ector , Luc. Public Research Centre - Gabriel Lippmann. Department of Environment and Agro-biotechnologies; Luxemburgo Fil: Schloss, Irene Ruth. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Université du Québec; Canadá